2016
DOI: 10.1021/acs.biomac.6b01159
|View full text |Cite
|
Sign up to set email alerts
|

Specific Uptake of Lipid-Antibody-Functionalized LbL Microcarriers by Cells

Abstract: The modular construction of Layer-by-Layer biopolymer microcarriers facilitates a highly specific design of drug delivery systems. A supported lipid bilayer (SLB) contributes to biocompatibility and protection of sensitive active agents. The addition of a lipid anchor equipped with PEG (shielding from opsonins) and biotin (attachment of exchangeable outer functional molecules) enhances the microcarrier functionality even more. However, a homogeneously assembled supported lipid bilayer is a prerequisite for a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 42 publications
0
14
0
Order By: Relevance
“…From previous investigations it has been shown that a significant interaction between SLB-LbL microcarriers and Vero cells does not occur prior to 3 h post coincubation. 44 However, cellular internalization of lipid-enveloped viruses via clathrin-mediated endocytosis occurs within a few minutes. 45 Therefore, the interaction of the VSV-LbL microcarriers was monitored by means of FC over relatively short time frames of 30 and 60 min (comparing red fluorescent cells and nonfluorescent cells).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…From previous investigations it has been shown that a significant interaction between SLB-LbL microcarriers and Vero cells does not occur prior to 3 h post coincubation. 44 However, cellular internalization of lipid-enveloped viruses via clathrin-mediated endocytosis occurs within a few minutes. 45 Therefore, the interaction of the VSV-LbL microcarriers was monitored by means of FC over relatively short time frames of 30 and 60 min (comparing red fluorescent cells and nonfluorescent cells).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…LbL microcarriers were surface coated with an additional lipid bilayer. Therefore, liposomes were prepared as described according to Gose et al 15,44 POPS and POPC were mixed in a 1:1 molar ratio. The dried lipids were rehydrated with 522 μL of PBS (without calcium and magnesium) to obtain a 10.2 mM lipid solution.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…As a platform for the VSV, the LbL microcarriers were additionally equipped with a supported lipid bilayer (SLB). Preparation of liposomes as a prerequisite for an SLB was performed as described in Gose et al 39 LbL microcarriers equipped with an SLB were named as SLB-LbL microcarriers.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…To analyze the processing of the supported lipid bilayer of the LbL microcarrier after internalization, the SLB was equipped with 0.1 mol % of PE-RITC. 39 Again, cells were seeded in chamber slides with a density of 5 × 10 4 cells per well. Microcarriers were applied to cells at a 5:1 ratio, and cells were stained with Hoechst33342 after the respective time points.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…After targeting is being achieved, the actual uptake mechanism allowing for encapsulated cargo to be delivered to the cell, as well as the uptake specificity must be investigated in detail. 38,58 It is known that particle size, shape, and mechanical properties could influence the interaction with cells and uptake substantially. 59,60 If the capsules are taken up by cells via the endocytic pathway, which is the major uptake mechanism of cells for larger entities, their endosomal escape can be facilitated by several viral and bacterial proteins, synthetic biomimetic peptides, polymers, etc.…”
Section: ■ Conclusionmentioning
confidence: 99%